2015
DOI: 10.1097/phh.0000000000000124
|View full text |Cite
|
Sign up to set email alerts
|

What Does a Performance Measurement System Tell Us About the National Comprehensive Cancer Control Program?

Abstract: Context The National Comprehensive Cancer Control Program (NCCCP) performance measurement system seeks to understand both the processes that funded programs undertake with their respective coalitions to implement the objectives of their cancer plans and outcomes of those efforts. Objective To identify areas of achievement and technical assistance needs of NCCCP awardees. Design Program performance was assessed through surveys completed by program directors on performance indicators in 2009 and 2010 and que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 24 publications
0
10
0
2
Order By: Relevance
“…In 2009, NCCCP programs reported that they were working in partnership with more than 6,000 organizations and individuals, including government public health programs (94%), academic (94%) and professional (84%) organizations, cancer survivors (63%), and political leaders (51%) ( 11 ). The programs often leverage the resources of these partners (eg, donated time, financial support, subject matter expertise) to develop and implement interventions in cancer control plans ( 24 ); therefore, CCC partners are crucial to accelerating the adoption of EBPs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2009, NCCCP programs reported that they were working in partnership with more than 6,000 organizations and individuals, including government public health programs (94%), academic (94%) and professional (84%) organizations, cancer survivors (63%), and political leaders (51%) ( 11 ). The programs often leverage the resources of these partners (eg, donated time, financial support, subject matter expertise) to develop and implement interventions in cancer control plans ( 24 ); therefore, CCC partners are crucial to accelerating the adoption of EBPs.…”
Section: Discussionmentioning
confidence: 99%
“…This percentage is higher than the level of partner involvement in implementing interventions reported by NCCCP program directors in previous studies. Townsend and colleagues evaluated performance measures data reported by NCCCP awardees to CDC as a condition of their funding ( 24 ). In their analysis, 60% of programs reported that their partners had implemented at least one priority strategy from their jurisdiction’s cancer control plan from June 2008 through June 2009.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluation efforts at the national level in the early years of the program, including the development and fielding of a performance measurement system and cancer plan assessment tool, provided valuable information regarding technical assistance needs and improvements that could be made across all participants [16][17][18]. Results from surveys in 2009 and 2010 showed that a majority of programs had successfully implemented at least one community-or organization-level change strategy; however, not all programs were using only evidence-based interventions, and there were few participants linking their activities to cancer impact [19]. Recognizing that participants needed assistance in these areas, as well as in communicating their efforts, CDC developed an overarching set of strategic priorities to guide the cancer public health practice of all NCCCP participants, regardless of their unique nature and cancer burden [20].…”
Section: The National Comprehensive Cancer Control Programmentioning
confidence: 99%
“…The Centers for Disease Prevention and Control’s (CDC) National Comprehensive Cancer Control Program (NCCPC) fund 65 awardees (states, territories, Pacific Island jurisdictions, and tribes/tribal organizations) in 69 Comprehensive Cancer Control (CCC) programs to develop and implement CCC plans via CCC coalitions, alliances, or consortia of program stakeholders ( 1 , 2 ). CCC is a process through which communities and partner organizations pool resources to reduce the burden of cancer by reducing cancer risk, finding cancers earlier, improving treatments, increasing the number of people who survive cancer, and improving the quality of life for cancer survivors ( 2 ).…”
Section: Introductionmentioning
confidence: 99%